(untitled) (Agronomy Journal of Nepal, 2021)
There has been growing import of fine and aromatic rice in Nepal in recent years. The inherent quality of different rice varieties could be one factor over consumer preference while proper packing and branding could be other factors. Most of the Nepalese rice varieties have not been able to penetrate the market as commercial brands and local landraces are gradually getting popular due to their inherent taste, aroma nutritional value. A study was conducted by the Center for Crop Development and Agro-biodiversity Conservation (CCDABC) in the year 2018/19 to compare the chemical compositions of different Nepalese rice varieties and imported brands, which were collected from major markets of different districts of Nepal. The study was aimed in understanding the chemical composition of these varieties and to know if the growing preference over imported fine and aromatic varieties had better chemical parameters over Nepalese varieties. The study revealed that higher content of zinc was observed in local varieties than in other varieties and brands. It ranged from 10.9 to 13.9 mg/kg in imported brands and from 9.7 to 17.6 mg/kg in released varieties. The highest crude protein was observed in the Dawat (12.64 %), one of the Indian brands and the lowest in Radha 4 (6.02 %) Nepalese released variety is commonly grown in the country. Average crude protein in Nepalese brands, imported brands, released varieties and local varieties were found as 11.22 %, 10.38, 8.62 % and 7.41 % respectively. Local varieties showed the highest crude fat (average 2.19 %) content followed by released varieties (average 1.17 %) and Nepalese brands (average 0.51 %). Likewise, crude fibre and total ash contents in local varieties were observed as 0.96 % and 0.93 % respectively. Therefore, the study revealed that local varieties were found superior in terms of chemical and nutritional perspective (total ash, crude fibre, crude fat and zinc) over other varieties and brands found in Nepal. In terms of protein, Nepalese brands were found superior over other varieties and brands.